UNDERGRADUATE STUDENTS SELF-CONCEPT AND THEIR MATHEMATICS PROCEDURAL KNOWLEDGE: THE RELATIONSHIP - Muhammad Win Afgani; Didi Suryadi; Jarnawi Afgani Dahlan (Jurnal Infinity, 2019)
This study aimed to explain the relationship between self-concept and mathematics procedural knowledge among undergraduate students of mathematics education. This study investigated the affective and cognitive aspect of students in the learning of mathematics. The method in this study surveyed with non-probability sampling technique. The subjects were 133 undergraduate students of mathematics education from public and private university in Palembang, Indonesia. 66 of them were undergraduate students in public university. The rest of them were undergraduate students in a private university. The instruments that were used are questionnaire of self-concept and essay test of mathematics procedural knowledge. The result from the Spearman Rank Correlation showed Sig. = 0.006 < 0.05. From that result, we conclude that there is a significant relationship between undergraduate students’ self-concept and their mathematics procedural knowledge.